Into the unknown: explorations in development practice - and Chambers, Robert (Practical Action Publishing, 2014)
Into the Unknown reflects on the journey of learning, and encourages readers to learn from observation, curiosity, critical feedback, play and fun. This book will be of interest to development professionals, including academics, students, NGO workers and the staff of international agencies